The fracture of brittle materials : testing and analysis - Freiman, S. W. (John Wiley & Sons, 2012)
'Supports the use and development of strong, fracture-resistant, and mechanically reliable ceramic materials. The Fracture of Brittle Materials thoroughly sets forth the key scientific and engineering concepts underlying the selection of test procedures for fracture toughness, strength determination, and reliability predictions. With this book as their guide, readers can confidently test and analyze a broad range of brittle materials in order to make the best use of existing materials as well as to support the development of new materials. The authors explain the importance of microstructure in these determinations and describe the use of quantitative fractography in failure analysis."--